The Role of Teachers in Improving Students' Cognitive Learning Outcomes in Theme 8 Subtheme 2 in Class IV - Oktriawina, Fatma (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2019)
This research explores the role of teachers in improving students' cognitive learning outcomes in theme 8 subtheme 2 in class IV B SD Negeri 13/I Muara Bulian. Conducted in the even semester of the 2018/2019 academic year with a qualitative phenomenological approach. The class IV B teacher was the data source using data collection techniques through observation, interviews and documentation. The research results show that teachers act as teachers with thorough preparation, managers who create conducive learning conditions, innovators who refresh learning activities, facilitators who provide support, and evaluators who provide feedback to students. Through interviews, observation and documentation activities, it has been proven that these roles contribute to improving students' cognitive learning outcomes in theme 8 subtheme 2.